Performance analysis of a modular adsorption cooling system with sonic vibration in the adsorber - W. Ritthong (2018)
This article presents a performance evaluation of an adsorption cooling system using activated carbon-methanol as the working pair. The desorption process was enhanced by a sonic-wave generator attached to the center of the side of the adsorber. The results show that the sonic-wave activation reduced the cycle time of the heating-condensation process and improved the system performance in terms of coefficient of performance, specific cooling power, and volumetric capacity power, of which the highest achieved for this system were 0.619, 229.15 W/kg, and 17.61 cm3/W, respectively. © Taylor and Francis Group, LLC.